2011
DOI: 10.4061/2011/924605
|View full text |Cite
|
Sign up to set email alerts
|

Bladder, Bowel, and Sexual Dysfunction in Parkinson's Disease

Abstract: Bladder dysfunction (urinary urgency/frequency), bowel dysfunction (constipation), and sexual dysfunction (erectile dysfunction) (also called “pelvic organ” dysfunctions) are common nonmotor disorders in Parkinson's disease (PD). In contrast to motor disorders, pelvic organ autonomic dysfunctions are often nonresponsive to levodopa treatment. The brain pathology causing the bladder dysfunction (appearance of overactivity) involves an altered dopamine-basal ganglia circuit, which normally suppresses the micturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 236 publications
(344 reference statements)
3
89
1
5
Order By: Relevance
“…Slow gastric transport leads to delayed jejunal absorption, resulting in a delayed plasma levodopa peak. This slow gastric transport can be attributed to myenteric plexus pathology in PD [10], where altered balance of cholinergic/5-HT4 serotonergic excitation and D2 dopaminergic inhibition might occur [11]. Although peripherallyacting dopamine on the bowel motility produced conflicting results [11], centrally-acting levodopa did not worsen colonic transit in PD patients [12].…”
Section: Discussionmentioning
confidence: 97%
“…Slow gastric transport leads to delayed jejunal absorption, resulting in a delayed plasma levodopa peak. This slow gastric transport can be attributed to myenteric plexus pathology in PD [10], where altered balance of cholinergic/5-HT4 serotonergic excitation and D2 dopaminergic inhibition might occur [11]. Although peripherallyacting dopamine on the bowel motility produced conflicting results [11], centrally-acting levodopa did not worsen colonic transit in PD patients [12].…”
Section: Discussionmentioning
confidence: 97%
“…This will be explored in future experiments. It is possible that lumbosacral DA neurons modulate other pelvic organ functions, as a dysfunctional DA system results in abnormal sexual and bowel function and visceral pain (Shulman et al, 2001; Sakakibara et al, 2011; Jarcho et al, 2012), and is therefore valuable for researchers to pursue.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupting DA signaling results not only in motor dysfunction but also in autonomic disorders (Shulman et al, 2001; Sakakibara et al, 2011). For instance, irritable hyperactive bladder symptoms, such as urinary urgency, frequency, and incontinence, often occur when midbrain DA neurons are damaged in Parkinson’s disease (PD) (Winge and Fowler, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract dysfunction can be tested in animal models by demonstrating evidence of parasympathetic and somatic dysfunction, manifested by reduced bladder capacity, external sphincter relaxation, detrusor weakness, and urethral obstruction [115]. In a study of cats, it is found that stimulation of subthalamic nucleus can manifest inhibitory effects on the micturition reflex [116].…”
Section: Urinary Tract Dysfunctionmentioning
confidence: 99%